Impact of Work Stress, Communication, and Work Environment on Dealer Employee Performance - Muhammad Naufal Riaztantyo; Vera Firdaus (Indonesian Journal of Cultural and Community Development, 2023)
This study aimed to investigate the influence of work stress, communication, and work environment on employee performance in the automotive industry. Employing a quantitative research design, data was collected through a questionnaire from a sample of 100 employees at a Honda dealership in Sidoarjo, Indonesia. Various data analysis techniques, including validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing, were utilized. The findings revealed that communication and work environment had a positive and significant impact on employee performance, while work stress had a negative and significant effect. Moreover, the results demonstrated that employee performance was significantly influenced by work stress, communication, and work environment collectively. These findings contribute to our understanding of the factors influencing employee performance and have implications for managerial practices aimed at improving employee well-being and organizational productivity. Highlights: The study investigates the impact of work stress, communication, and work environment on employee performance in the automotive industry. Communication and work environment positively influence employee performance, while work stress negatively affects it. The findings emphasize the importance of addressing work stress, improving communication, and fostering a positive work environment to enhance employee performance in the automotive industry. Keywords: Work stress, Communication, Work environment, Employee performance, Automotive industry.